URGENSI PELAKSANAAN SUMPAH JABATAN PEGAWAI NEGERI SIPIL DALAM PASAL 1 PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 21 TAHUN 1975 DALAM PERSPEKTIF NEGARA HUKUM DI INDONESIA - M. N. Julnafid; Rika Lestari; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In Kuantan Singingi Regency, specifically Inuman District, there are still many cultures andtraditions, one of which is "bagito". Bagito means accepting or adopting a child who is not one's owndescendant through a traditional procession with the intention of treating and caring for the child likeone's own child, then the child is called anak Bagito, the term for adopted children in Inuman District.This research is related to the implementation of Malay Kuantan customary inheritance for Bagito'schildren in Inuman District, Kuantan Singingi Regency. The purpose of this study is to find out howinheritance is divided according to customary law in Inuman District, Kuantan Singingi Regency andwhat are the criteria for a Bagito (adopted child) not to receive inheritance rights according to theninik mamak.This type of research is a sociological law research, because it is based on field research,namely by collecting data from interviews and literature studies that have to do with problems usingqualitative data analysis, producing descriptive data, and concluded with a deductive thinkingmethod.From the results of the study it was concluded that, first, the distribution of inheritanceaccording to custom has actually been carried out properly, in accordance with the rules of customarylaw. Inheritance in customary law in Inuman District can also be given to Bagito's children who havegone through a traditional ceremonial procession, Bagito's children have the position of legal heirs oftheir adoptive parents and have special rights, that is, they can still become heirs of their biologicalparents. Second, the criteria for a Bagito child not to receive inheritance rights according to the ninikmamak of Inuman District, Kuantan Singingi Regency, in terms of inheritance, Bagito's child gets thesame share as his biological child. However, according to the ninik mamak, there are 4 (four)provisions for Bagito's children not receiving inheritance rights, namely not respecting and lovingtheir adoptive parents during their lifetime, not having a good relationship with relatives of theiradoptive parents, changing beliefs or religions, and not obeying customary law. If one of them is doneaccording to the ninik mamak, Bagito's children do not have the right to inherit from their adoptiveparents. Of the 3 (three) cases of Bagito's child inheritance disputes, there is 1 (one) case of Bagito'sson not receiving inheritance rights according to ninik mamak criteria. The criteria of the ninikmamak apply in the distribution of inheritance to Bagito's children.Keywords : Customary Inheritance – Bagito’s Son – Customary Law